2022
DOI: 10.1088/1755-1315/985/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porang Flour and Low-Calorie Sugar Concentration on The Physico-Chemical Characteristics of Jelly Drinks

Abstract: Jelly drink is a fiber-rich drink sourced from hydrocolloid which aims to provide a distinctive viscosity. Hydrocolloids commonly used in the production of jelly drinks are agar, carrageenan, and glucomannan. The use of porang flour in the production of jelly drinks has not been widely reported. This study aims to determine the effect of porang flour and low-calorie sugar concentrations on jelly drinks. This study was prepared using a completely randomized design with a concentration of porang flour (0.25%; 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…Research (Herawati and Kamsiati, 2022) supports the fact that porang flour has a dietary fiber content of 3.55%. This study's dietary fiber amount is consistent with studies by Suryana et al (2022), which found that jelly drinks containing porang powder had a fiber content of about 0.145%. According to (Aller et al, 2011), glucomannan in porang flour is a source of dietary fiber and may increase viscosity (Herawati and Kamsiati, 2022;Aller et al, 2011), crude dietary fiber is part of food that cannot be digested by the body or hydrolyzed by chemicals such as strong acids and bases.…”
Section: Dietary Fiber Contentsupporting
confidence: 91%
See 3 more Smart Citations
“…Research (Herawati and Kamsiati, 2022) supports the fact that porang flour has a dietary fiber content of 3.55%. This study's dietary fiber amount is consistent with studies by Suryana et al (2022), which found that jelly drinks containing porang powder had a fiber content of about 0.145%. According to (Aller et al, 2011), glucomannan in porang flour is a source of dietary fiber and may increase viscosity (Herawati and Kamsiati, 2022;Aller et al, 2011), crude dietary fiber is part of food that cannot be digested by the body or hydrolyzed by chemicals such as strong acids and bases.…”
Section: Dietary Fiber Contentsupporting
confidence: 91%
“…The decrease in water content in fermented goat milk causes the free water content used by bacteria to grow to be reduced, thus inhibiting the growth of lactic acid bacteria. It is supported by research Suryana et al (2022) that protein can form gels where polymer chains create networks and then trap water to form a strong and rigid structure. The ability of proteins to bind water in substantial amounts may constrict the interparticle space, thereby entrapping and solidifying the water within the solution.…”
Section: Results and Discussion Total Lactic Acid Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Hasil ANOVA untuk semua respon total gula dan stabilitas susu kedelai akibat pengaruh formula susu kedelai, glukomanan porang dan gula aren dapat dilihat pada Glukomanan merupakan polisakarida tersusun atas molekul glukosa dan mannosa yang merupakan senyawa hidrokolloid yang menyebabkan gel pada suatu system campuran makanan. Glukomanan kebanyakan merupakan ingredient utama pada produk minuman seperti: jelly drink (Suryana et al, 2022). Teori ini sesuai mendukung data Tabel 3, dimana penambahan tepung GM porang pada susu kedelai (AB) dan susu kedelai yang diberi GM porang dan gula aren (BC) berpengaruh nyata terhadap kestabilan susu kedelai.…”
Section: Analisis Kurva Respon Permukaanunclassified